Математичне моделювання ультразвукових сигналів у застосуваннях дефектоскопії - Огір, О. О. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The investigation of mathematical models of ultrasonic signals used in acoustic imaging systems forming the internal structure of controlled materials and media objects energy industry. Such models make it possible to take into account all effects in wave processes: radiation and reflection of waves, phenomena of interference and diffraction of waves, wave type transformations during reflection and the appearance of damped waves at the interfaces of opaque media.
Keywords: хвильові рівняння; хвильові процеси; теорія розсіяння; ехосигнали